2011
DOI: 10.1093/cid/cir436
|View full text |Cite
|
Sign up to set email alerts
|

Does Monastic Life Predispose to the Risk of Saint Anthony's Fire (Herpes Zoster)?

Abstract: This study failed to demonstrate an increased risk or earlier onset of zoster in members of CMO not exposed to VZV, compared with that in the GP. Although adults highly exposed to VZV could have a reduced risk of zoster, compared with the GP, our results suggest that the opposite is not true: adults not exposed to VZV are not at increased risk of zoster when compared with the GP, challenging the relevance of the assumptions and forecasts of current epidemiological models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…Exposure to varicella might reduce the risk of zoster [37,38] and on the other hand, its absence would lead to an increase of herpes zoster [34,39]. Although this possible negative effect of the two-dose universal vaccination programme has not been taken into account in this study, recent studies have not demonstrated a relationship between varicella vaccination and increase of zoster disease in the general population [20,40,41]. Moreover, others have reported a reduction in zoster incidence in vaccinated [40,42].…”
Section: Discussionmentioning
confidence: 64%
“…Exposure to varicella might reduce the risk of zoster [37,38] and on the other hand, its absence would lead to an increase of herpes zoster [34,39]. Although this possible negative effect of the two-dose universal vaccination programme has not been taken into account in this study, recent studies have not demonstrated a relationship between varicella vaccination and increase of zoster disease in the general population [20,40,41]. Moreover, others have reported a reduction in zoster incidence in vaccinated [40,42].…”
Section: Discussionmentioning
confidence: 64%
“…If periodic exposure to children with varicella does not reduce the incidence of HZ, there is no reason to force children and their parents to cope with varicella or to risk the damage that varicella can do to immunocompromised hosts. In a French study of isolated middle-aged individuals living in a convent and a monastery without exposure to children, the incidence of HZ was not higher than that of the population living with children in the neighboring village (178). Although the incidence of HZ is increasing in the United States, the increase began long before the varicella vaccine was licensed in 1995 (179,180).…”
Section: Zoster Vaccinementioning
confidence: 97%
“…A large-scale European serology has indicated a lower HZ incidence by age in countries where varicella force of infection (FOI) is higher [2]. Nonetheless, contrary evidence also exists [9].…”
Section: Introductionmentioning
confidence: 99%